What prevents Readmission? - Antony, Daly (International Journal of Psychosocial Rehabilitation, 2017)
A series of interviews was carried out by a community recovery team in an inner-city area of the United Kingdom to discover what its services users believe helps prevent readmission to mental hospital. The aim was to increase understanding of service user perspectives of readmission and give insight into ways to reduce readmission rates. A qualitative thematic analysis method was used to analyse the data following a series of semi-structured interviews with service users. The results showed the value of developed social support networks, medication concordance and non-use of drugs/alcohol in service user perspectives. The conclusions were that community rehabilitation teams need to consider service user’s understandings of hospital and its role in their lives when developing interventions.